О роли Восточно-Сибирского шельфа в современном цикле метана и глобальном изменении климата - Шахова Н. Е. Наталья Евгеньевна; Семилетов И. П. Игорь Петрович; Салюк А. Н.; Бельчева Н. Н.; Космач Д. А.; Сергиенко В. И. (2008, 2008)
Заглавие с экрана